PCR-SSCP and Sequencing of CXCR1 (IL8RA) Gene in Indian Water Buffalo - Kaur, Manpreet; Ramneek, -; Mukhopadhyay, C.S.; Arora, Jaspreet Singh (International Journal of Applied Sciences and Biotechnology, 2016)
Genetic markers associated with inflammatory responses could help in selecting the animals susceptible/tolerant to mastitis. The selective breeding assisted by these markers could help to reduce the huge economic losses that are posed by various forms of mastitis. Onepossible marker is CXCR1, a chemokine receptor that is required for neutrophil migration to infection site. Therefore the present study was planned to identify genetic polymorphism (if any)in CXCR1 gene and associate it with subclinical mastitis in Riverine buffalo of Northern India. For this,two hundred healthy lactating water buffalo were randomly chosenfrom the herds maintained by various farmers in Kapurthala District of Punjab, India.Blood and milk samples of selected buffaloes werecollected. Screening of the animals for sub clinical mastitis was done by SCC and CMT assays of milk samples.Genomic DNA was isolated from blood samples by phenol chloroform method. The DNA of good quality was used for further analysis. PCR-SSCP was used to explore the polymorphism in 311 bp fragment of partial exon2 of CXCR1 gene. The 311 bp fragment of CXCR1 gene was found to be monomorphic in all the DNA samples screened of Indian water buffalo. Int J Appl Sci Biotechnol, Vol 4(2): 228-232